THE CLINICAL CASE OF PRIMARY PROGRESSIVE APHASIA - Natalya V. Shuleshova; Aleksey V. Sizov; Irina V. Kupriianova; Victoria V. Zvereva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2019)
The article described the rare clinical case of the patient with probable transmissible encephalopathy (Creutzfeldt–Jakob disease) in whom rapidly forming primary progressive aphasia was the herald clinical feature, and motor and sensory functions were preserved. Creutzfeldt–Jakob disease was diagnosed, and it was confirmed by clinical picture with fast progression of the disease, together with neurovisualization (brain magnetic resonance imaging, FLAIR and DWI options) and electroencephalography pattern. Other possible causes of primary progressive aphasia were excluded.